Principals’ Administrative Skills and Teachers Effectiveness in Public Secondary Schools in Ilorin Metropolis, Kwara State - Ogbudinkpa, ljeoma Charity; Oluwalola, Felicia Kikelomo (International Journal of Educational Management, 2025)
This paper investigated the relationship between Administrative Skills and Teachers Effectiveness in public secondary schools in Ilorin South Local Government, K war a State. The research design was descriptive survey, stratified random sampling was used to select a total of 200 participants out of 1178 teachers from 21 public secondary schools in Ilorin South Local Government Area. Questionnaires titled Principals Administrative Skill Questionnaire (PAS) and Teachers Effectiveness Questionnaire ([EQ) was used to collect data/or the study. Five research questions were raised to guide the study, one main hypothesis and three null hypotheses were tested at 0. 05 level of significance. The data were analysed using Pearson product moment correlation statistics and multiple regression statistics. The findings revealed among others that proper information channel was used by principals to enhance necessary decision making in schools; it showed that management information system impacted positive significance on teachers effectiveness, furthermore, ii revealed that communication skills was statistica/ly significant on teachers effectiveness. It was concluded that, principals administrative skills should incorporate good communication network for proper information dissemination, as this will enhance necessary decision making and impact positively on teachers’ effectiveness. Based on the findings, it was recommended among others that principals should increase the use of proper communication channels to enhance teachers’ effectiveness.